Sensory Nociceptive Neurons Contribute to Host Protection During Enteric Infection With Citrobacter rodentium. (21st January 2020) - Ramirez, Valerie T; Sladek, Jessica; Godinez, Dayn Romero; Rude, Kavi M; Chicco, Pamela; Murray, Kaitlin; Brust-Mascher, Ingrid; Gareau, Melanie G; Reardon, Colin
Abstract: Background: Neurons are an integral component of the immune system that functions to coordinate responses to bacterial pathogens. Sensory nociceptive neurons that can detect bacterial pathogens are found throughout the body with dense innervation of the intestinal tract. Methods: In this study, we assessed the role of these nerves in the coordination of host defenses to Citrobacter rodentium . Selective ablation of nociceptive neurons significantly increased bacterial burden 10 days postinfection and delayed pathogen clearance. Results: Because the sensory neuropeptide CGRP (calcitonin gene-related peptide) regulates host responses during infection of the skin, lung, and small intestine, we assessed the role of CGRP receptor signaling during C rodentium infection. Although CGRP receptor blockade reduced certain proinflammatory gene expression, bacterial burden and Il-22 expression was unaffected. Conclusions: Our data highlight that sensory nociceptive neurons exert a significant host protective role during C rodentium infection, independent of CGRP receptor signaling. Abstract : Sensory neurons are important in coordinating the host mucosal immune response to the enteric bacterial pathogen Citrobacter rodentium .